Theological Investigatinos. (vol. .XVii ): Jesus, Man and the Church - Chethimattam, John B (Journal of Dharma, 1981)
Karl Rahner Theological Investigatinos. (vol. .rvii ) : Jesus, Man and the Church transl. Margaret London : Darton, Longman & Todd, 1981, pp. 260, £ 14.50